2013
DOI: 10.1021/jp311547g
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Ionic Conductivity of Sr2+-Doped CeP2O7 Electrolyte in Humid Atmosphere

Abstract: Sr2+-doped cerium pyrophosphate (Ce1–x Sr x P2O7, x = 0.05, 0.1, 0.15, and 0.2) electrolytes are synthesized by digesting cerium oxide and strontium nitrate with 85% H3PO4. The ionic conductivity behavior of Ce1–x Sr x P2O7-sintered pellets is analyzed by electrochemical impedance spectroscopy in a dry and humid air atmosphere. The time-dependent variation of ionic conductivity during humidification process and the variation of conductivity with temperature are studied. In humid atmosphere in the 90–230 °C ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 23 publications
3
42
0
Order By: Relevance
“…22,23 In order to minimize the effect of incomplete initial humidification, all CGP samples were humidified for relatively longer duration (>100 h) at 90 • C until a stable EIS response is obtained. Figure 9a and 9b show Cole-Cole plot for EIS measurement on CGP at 90 and 190 • C in humidified air atmosphere.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 In order to minimize the effect of incomplete initial humidification, all CGP samples were humidified for relatively longer duration (>100 h) at 90 • C until a stable EIS response is obtained. Figure 9a and 9b show Cole-Cole plot for EIS measurement on CGP at 90 and 190 • C in humidified air atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…Gd 3+ -doped CeP 2 O 7 were synthesized by digesting GDC powder with 85% H 3 PO 4 via slight modification of the earlier reported single step digestion procedure. 14,22 Briefly, the GDC powder and H 3 PO 4 were mixed in different P/(Ce+Gd) molar ratio (2.3-2.8) in a covered alumina crucible at ∼95 • C for ∼8 h with constant stirring using magnetic stirrer to get a highly viscous paste. The temperature was then raised to ∼150 • C to get a dry yellow solid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have been working on the synthesis and characterization of cerium pyrophosphates for the application as electrolyte in low-temperature PCFCs [8][9][10]. Though the cerium pyrophosphates are thermally unstable at 4400 1C and therefore their sintering at the higher temperature is avoided [10,11], it has been observed that they give fairly dense specimens even on sintering at temperatures $ 400 1C [5,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Though the cerium pyrophosphates are thermally unstable at 4400 1C and therefore their sintering at the higher temperature is avoided [10,11], it has been observed that they give fairly dense specimens even on sintering at temperatures $ 400 1C [5,[8][9][10][11]. Considering the fact that pyrophosphates of cerium and tin are generally isomorphous, with both having cubic lattice and Pa3 space group [12,13], it is expected that on partially replacing Sn 4 þ ion in SnP 2 O 7 by Ce 4 þ ion, Ce 4 þ ion would be easily incorporated into tin pyrophosphate lattice, although the ionic radius of Ce 4 þ ion (r=0.87 Å) is larger than that of Sn 4 þ ion (r=0.69 Å) [14], and improve the sinterability of tin pyrophosphate.…”
Section: Introductionmentioning
confidence: 99%